Investigating the proactive avoidance of pre-emption conflicts with emergency vehicle emergency vehicle response times and route selection integration - Broeksma, Cornelis Reitz Daniël (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.